Wilayah Perbatasan Kalimantan Barat: Sumber Sejarah dan Permasalahannya - Marihandono, Djoko (Paradigma: Jurnal Kajian Budaya, 2011)
The research deals with the region in the two-area Kalimantan/Borneo border with Malaysia; in the east, Nunukan, and in the west, Entikong. The border problem rises when a geopolitical interest of Indonesia and Malaysia overwhelms the traditional ways of farming and trade that have existed even before the British and Dutch colonial governments executed their administrative systems by dividing them into security and prosperity belts, despite the existing active roles of local authorities to manage their resources. Now, the heritage of the rich natural resources and the mobile population, becomes a major issue of dispute. The available resources, such as fish, coal and gold; crops, such as chocolate, nutmeg and rubber; prospective reservation areas for tourism, such as the Indonesian national parks in Danau Sentarum, Gunung Niut, and Betung Karihun, become a vulnerable target for exploitation. These crucial zones have been a part of an intricate interwoven eco-region. The paper uses the colonial British and Dutch archieves and other literature to describe the historic conflict of interest for exploitation and extraction of the resources, and the post-independent sources which talked about the endless Malaysian intrusions faced by the Indonesian government.